2020
DOI: 10.1007/s11120-020-00802-2
|View full text |Cite
|
Sign up to set email alerts
|

Acclimation of Chlamydomonas reinhardtii to extremely strong light

Abstract: Most photosynthetic organisms are sensitive to very high light, although acclimation mechanisms enable them to deal with exposure to strong light up to a point. Here we show that cultures of wild-type Chlamydomonas reinhardtii strain cc124, when exposed to photosynthetic photon flux density 3000 μmol m−2 s−1 for a couple of days, are able to suddenly attain the ability to grow and thrive. We compared the phenotypes of control cells and cells acclimated to this extreme light (EL). The results suggest that genet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 71 publications
1
18
0
Order By: Relevance
“…The same trend was discovered for the Car/Chl ratio indicative of PSA acclimation to the excessive light [23,44,45]. The content of individual Cars meas ured by HPLC was also insensitive to the chilling: neither VAZ nor de epoxidized VAZ xanthophylls (reflected as the DE value) revealed statistically significant changes.…”
Section: Resultssupporting
confidence: 68%
“…The same trend was discovered for the Car/Chl ratio indicative of PSA acclimation to the excessive light [23,44,45]. The content of individual Cars meas ured by HPLC was also insensitive to the chilling: neither VAZ nor de epoxidized VAZ xanthophylls (reflected as the DE value) revealed statistically significant changes.…”
Section: Resultssupporting
confidence: 68%
“…Algae grown under various light intensities show changes in biomass formation rate, pigment and lipid content, fatty acid composition, and ratio. For this purpose, various researchers have studied a fairly wide range of light intensity: from 5 to 3500 µmol photons m −2 s −1 [31,43,47,53,[77][78][79][80].…”
Section: Optimal and Photoinhibiting Light Intensitymentioning
confidence: 99%
“…Recent studies have shown that the strains Chlamydomonas reinhardtii cc124 and Chlorella ohadii, which are able to grow under very strong lighting-3000 and 3500 µmol photons m −2 s −1 , respectively, exhibit high resistance to photoinhibition [31,80]. The strain Chlorella ohadii was isolated from a biological sand crust from the Sinai Desert in the northwestern Negev, Israel [31], and Chlamydomonas reinhardtii cc124 is a laboratory strain widely used as a wild type.…”
Section: Optimal and Photoinhibiting Light Intensitymentioning
confidence: 99%
“…The highest light intensity at which a phototroph (an alga in this case) gains energy (i.e., the highest intensity at which the costs of PSII repair do not exceed the energy that can be obtained by photosynthesis) depends on the species (Murphy et al 2017). In addition, acclimation allows for example the green alga Chlamydomonas reinhardtii to grow at the extreme PPFD of 3,000 μmol(photon) m -2 s -1 (Virtanen et al 2021). It is concluded that all the tested algal species were able to grow under the light intensity used in the present study [200 μmol(photon) m -2 s -1 ].…”
Section: What Is the Relationship Between Psii Photoinhibition And Growth Rate During Continuous Culture?mentioning
confidence: 51%